Ali Smith's necessary-contingent, or navigating the global. Issue 4 (21st April 2018) - Evans, Joel
ABSTRACT: This essay begins by tracking down the various interplays between necessity and contingency to be found in two of Ali Smith's novels: The Accidental (2005) and There but for the (2012). As a result of these interplays, it will be suggested that Smith's novels produce a distinct concept, which is named the necessary-contingent. In fact, there are two versions of this concept, one to be found in The Accidental, and the other in There but for the . Firstly, the discussion will distinguish each variant, and articulate the philosophical, political and intertextual resonances and parallels on display respectively. Thus, we can establish more fully the implications of the concept generated by Smith's works. Secondly, the essay will seek to establish how the concept of the necessary-contingent is put to work in each novel. The arena where we find a concrete application for the concept, I will argue, is that of global space, and the individual's relation to it in the era of contemporary capitalism. Both novels, I suggest, produce a recognisable ethics of movement, which addresses not only some of the key issues surrounding so-called globalisation, but also demonstrates a further application of the concept extracted from Smith's work.